(untitled) (Journal of Comparative Social Work, 2012)
In this explorative article the relationship between social policy and social work will be in focus. The article discusses similarities and differences between Estonia and Norway.The empirical material consists of eight focus group interviews with social workers in the two countries. The aim of the study was to investigate to what extent the social work profession represents change agents in the social policy framework. The article looks at the differences and communalities in different years in the two countries. The authors conclude that social workers are important actors in implementing changes at the local level. They seem, however, to be more concerned about the daily encounters with the individual users than about the general policy framework.The main findings suggested that social workers in both countries see themselves as spokespersons for respect for and cooperation with the users while simultaneously arguing that social workers only to a very limited extent see the implementation of social policies as a part of their roles.